O pewnej metodzie dyskryminacji obiektów jakościowych - Kubus, Mariusz (On a method of discrimination of the nominal objects, 2006)
This paper contains an application of minimal logical trees in discriminant analysis. The logical tree is a graph of nominal attributes in a finite space. The minimal tree of every class - with the minimal number of nodes - is used for searching the class description space. Finally, an ordered list of classification rules is obtained. Using well known data sets, the classification accuracy is compared of the logical tree heuristic to CN2 and C4.5 algorithms.
Prace Naukowe Akademii Ekonomicznej we Wrocławiu. Taksonomia (13); 2006; nr 1126, s. 529-535